2018
DOI: 10.1089/thy.2017.0205
|View full text |Cite
|
Sign up to set email alerts
|

Lenvatinib for the Treatment of Radioiodine-Refractory Thyroid Cancer in Real-Life Practice

Abstract: Real-life patients with rDTC can benefit from lenvatinib treatment. AEs are frequent and should be closely monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
53
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 12 publications
21
53
2
3
Order By: Relevance
“…Other differences in the selection criteria apply as a result of the nature of retrospective studies, such as ECOG-PS 0-2, which independently reviewed radiologic evidence of progression within the previous 13 months. Several studies have evaluated the real-world clinical outcomes of lenvatinib for treating patients with RAI-r DTC in Europe , sunitinib (n = 10), vandetinib (n = 8), paclitaxel (n = 7), axitinib (n = 6), dabrafenib/trametinib combination (n = 5), and pembrolizumab (n = 2) [16][17][18][19]. Most of these studies concluded that there was a real-world clinical benefit of using lenvatinib to treat patients with RAI-r DTC in four European countries.…”
Section: Discussionmentioning
confidence: 99%
“…Other differences in the selection criteria apply as a result of the nature of retrospective studies, such as ECOG-PS 0-2, which independently reviewed radiologic evidence of progression within the previous 13 months. Several studies have evaluated the real-world clinical outcomes of lenvatinib for treating patients with RAI-r DTC in Europe , sunitinib (n = 10), vandetinib (n = 8), paclitaxel (n = 7), axitinib (n = 6), dabrafenib/trametinib combination (n = 5), and pembrolizumab (n = 2) [16][17][18][19]. Most of these studies concluded that there was a real-world clinical benefit of using lenvatinib to treat patients with RAI-r DTC in four European countries.…”
Section: Discussionmentioning
confidence: 99%
“…EBRT, embolisation, percutaneous treatment modalities) can be done for local control, without discontinuing MKIs [V, C]. Data on real life experiences with lenvatinib in DTC patients are now available and as expected, the drug's efficacy was not as good as that observed in highly selected RCT populations [100,101]. Other antiangiogenic agents have been tested as first-line therapy in phase II trials, with widely varying response rates ( [81,111].…”
Section: Management Of Advanced/metastatic Diseasementioning
confidence: 99%
“…Additionally, over the last decades, several new drugs and new methods of targeted therapy have been launched ( 12 ). A study conducted in France reported 75 patients with advanced radioactive iodine-refractory DTC could benefit from Lenvatinib with a median progression-free survival of 10 months ( 39 ), and this drug was recently approved by the U.S. Food and Drug Administration. More attention should be paid to targeted therapy with the better understanding of risk stratification of TC for precise treatment.…”
Section: Discussionmentioning
confidence: 99%